Functional analysis of the ligand binding site of EGF-receptor utilizing chimeric chicken/human receptor molecules. - Lax, I (1989)
The epidermal growth factor (EGF)-receptor is composed of an extracellular ligand-binding region connected by a single transmembrane region to the cytoplasmic kinase domain. In spite of its importance for understanding signal transduction, the ligand-binding domain of the EGF-receptor is not yet defined. We describe the identification of a major ligand-binding domain of the EGF-receptor by utilizing chimeras between the human EGF-receptor and the chicken EGF-receptor. This approach is based on the fact that murine EGF binds to the chicken EGF-receptor with 100-fold lower affinity as compared to the human EGF-receptor. Hence, the substitution of various domains of the chicken EGF-receptor by domains of the human EGF-receptor may restore the higher binding affinity towards EGF, characteristic of the human receptor. We show that chimeric chicken/human EGF-receptor, which contains domain III of the extracellular region of the human receptor, behaves like the human EGF-receptor with respect to EGF binding affinity and biological responsiveness. However, a chimeric chicken/human EGF-receptor containing domains I and II of the human receptor behaves like the chicken rather than the human EGF-receptor. Moreover, two different monoclonal antibodies which compete for the binding of EGF to EGF-receptor recognize specifically domain III of the human EGF-receptor. It is concluded that domain III which is flanked by the two cysteine-rich domains is a major ligand-binding domain of the EGF-receptor.